2004
DOI: 10.7748/ns2004.10.19.6.33.c3730
|View full text |Cite
|
Sign up to set email alerts
|

The research agenda for protocol-based care

Abstract: Protocols provide great potential to deliver best practice. However, questions remain about the benefits of protocol-based care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Success depends on the characteristics of the object of implementation and the context, as well as the individuals and activities involved [4,8]. The implementation process of CPs is seldom illuminated, the knowledge about the mechanisms through which CPs work remains insufficient and there is need of further knowledge from different contexts regarding the phenomenon [4,6,9–11].…”
Section: Introductionmentioning
confidence: 99%
“…Success depends on the characteristics of the object of implementation and the context, as well as the individuals and activities involved [4,8]. The implementation process of CPs is seldom illuminated, the knowledge about the mechanisms through which CPs work remains insufficient and there is need of further knowledge from different contexts regarding the phenomenon [4,6,9–11].…”
Section: Introductionmentioning
confidence: 99%
“…Patient outcomes, reduced length of stay and reduction of complications are used to determine the effectiveness of the standardization of care. [9] A review of the literature yielded few studies that implemented a nurse-driven protocol for administration of vasopressors through PIV access. A retrospective chart review of vasopressor administration through a PIV catheter demonstrated a 4% overall incidence of extravasation events when a strict safety protocol was not in place.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…SCPs may also help staff improve patient outcomes, reduce length of hospital stays, and enhance teamwork and record keeping (Rycroft‐Malone et al . , Deneckere et al . , Deng et al .…”
Section: Introductionmentioning
confidence: 99%